PENGARUH KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia pada Tahun 2018-2020) - Nisa Nafisa Sholikhah; Rina Trisnawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of dividend policy, firm size, profitability, institutional ownership and managerial ownership on firm value. The samping technique used was purposive samping with a sample of 30 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. This research data uses secondary data, namely the company’s financial statements obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used is multiple linear regression. The result showed that firm size, profitability, institusional ownership and managerial ownership had an effect on firm value. Meanwhile, dividend policy has no effect on firm value.